Aquinas on imitation of nature : source of principles of moral action - Golubiewski, Wojciech (The Catholic University of America Press, 2022)
"The author argues that it is possible to develop a metaphysical interpretation of Aquinas's doctrine of natural law that still deserves serious philosophical consideration today; examines Aquinas's theoretical reflections on the metaphysical and epistemological aspects of human natural goodness, applying them to moral contexts as found in the Secunda secundae"--